2004
DOI: 10.1097/01.sla.0000130723.81866.75
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Coloproctology of Great Britain and Ireland Study of Large Bowel Obstruction Caused by Colorectal Cancer

Abstract: Using prognostic models, it was possible to develop a risk-stratification index that accurately predicted survival in patients presenting with malignant large bowel obstruction. The methodology and model for risk adjusted survival can set the reference point for more accurate and reliable comparative analysis and be used as an adjunct to the process of informed consent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
220
2
16

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(256 citation statements)
references
References 16 publications
18
220
2
16
Order By: Relevance
“…Several studies have found the rates of morbidity and mortality in emergent colorectal surgery as 15-50% and 6-15%, respectively. These rates are reported as 4-14% and 1-7% in elective CRC surgery operations, respectively (30)(31)(32). The postoperative complication rate in our patients with emergent surgery was 91.1%, while this rate was 23.9% in the group with elective surgery, and the morbidity rate was higher in emergent patients.…”
mentioning
confidence: 48%
“…Several studies have found the rates of morbidity and mortality in emergent colorectal surgery as 15-50% and 6-15%, respectively. These rates are reported as 4-14% and 1-7% in elective CRC surgery operations, respectively (30)(31)(32). The postoperative complication rate in our patients with emergent surgery was 91.1%, while this rate was 23.9% in the group with elective surgery, and the morbidity rate was higher in emergent patients.…”
mentioning
confidence: 48%
“…The number of emergency surgical procedures in our study was zero since the few patients who presented as emergencies were stabilized and later referred for elective surgery. This decrease in morbidity and mortality rates among emergency patients treated electively was described by Tekkis et al where mortality rates were reduced from 20 to 12.9% in patients treated for obstructive colorectal cancer [13].…”
Section: Discussionmentioning
confidence: 57%
“…When applied specifically to colorectal surgery, these scoring systems have been found to overpredict mortality in elective surgical procedures and to underpredict mortality in elderly patients and in cases of emergency surgery [9][10][11][12]. This fact led to the development, in 2004, of the CR-POSSUM, which is specific for colorectal surgery [13]. It seems to be the most accurate scoring system, compared with the previous ones [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…These data also represent cases by type, but only those cases in which an obstruction (malignant large bowel) occurs and only for types Duke's B, C and Stage D (Tekkis et al 2004). We, therefore, define Z 3k , N 3 , Y 3k (x) and n 3 (x) and assume multinomial distributions similarly to the j = 2 case.…”
Section: Obstructed Cases Bymentioning
confidence: 99%